The flood estimation handbook initial experiences : BHS meeting, 8th March 2002. (Thomas Telford, 2002)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Minutes of a meeting held on 8 March 2003.
Keywords: Flood forecasting -- Congresses.; Flood control -- Congresses.; elektronické knihy; electronic books